IPTEK BAGI MASYARAKAT (IbM) KONVEKSI PAKAIAN CILEDUG - Suwandi, Arief; Amperajaya, Derajat; Nofierni, Nofierni (Universitas Esa Unggul, 2017)
AbstractCommunity service has been carried out by analyzing the situation which include: partners do not get used to bookkeeping finance, layout and arrangement of materials and machines in the production room has not been well organized and less clean, there is no final inspection for finished products, variations of convection products are still little, limited pattern-making for the product, and how to get an order that still relies on old customers. For that done devotion to the convection partner of clothing by helping to develop the business koneksekseks. The purpose of this community renewal activity is to provide knowledge about quality management and bookkeeping, effective production process, product and business development, and online promotion to business partners. The